Allosteric Activation of Bacterial Response Regulators: the Role of the Cognate Histidine Kinase Beyond Phosphorylation - Felipe Trajtenberg (American Society for Microbiology, 2014)
ABSTRACT Response regulators are proteins that undergo transient phosphorylation, connecting specific signals to adaptive responses. Remarkably, the molecular mechanism of response regulator activation remains elusive, largely because of the scarcity of structural data on multidomain response regulators and histidine kinase/response regulator complexes. We now address this question by using a combination of crystallographic data and functional analyses in vitro and in vivo, studying DesR and its cognate sensor kinase DesK, a two-component system that controls membrane fluidity in Bacillus subtilis. We establish that phosphorylation of the receiver domain of DesR is allosterically coupled to two distinct exposed surfaces of the protein, controlling noncanonical dimerization/tetramerization, cooperative activation, and DesK binding. One of these surfaces is critical for both homodimerization- and kinase-triggered allosteric activations. Moreover, DesK induces a phosphorylation-independent activation of DesR in vivo, uncovering a novel and stringent level of specificity among kinases and regulators. Our results support a model that helps to explain how response regulators restrict phosphorylation by small-molecule phosphoryl donors, as well as cross talk with noncognate sensors. IMPORTANCE The ability to sense and respond to environmental variations is an essential property for cell survival. Two-component systems mediate key signaling pathways that allow bacteria to integrate extra- or intracellular signals. Here we focus on the DesK/DesR system, which acts as a molecular thermometer in B. subtilis, regulating the cell membrane’s fluidity. Using a combination of complementary approaches, including determination of the crystal structures of active and inactive forms of the response regulator DesR, we unveil novel molecular mechanisms of DesR’s activation switch. In particular, we show that the association of the cognate histidine kinase DesK triggers DesR activation beyond the transfer of the phosphoryl group. On the basis of sequence and structural analyses of other two-component systems, this activation mechanism appears to be used in a wide range of sensory systems, contributing a further level of specificity control among different signaling pathways.